Biotin Encephalopathy and Basal Ganglia Lesions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Ten patients with biotin-responsive basal ganglia disease are reported from the King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia, and Brown University School of Medicine, Hasbro Children's and Rhode Island Hospitals, Providence, RI.